On-site generated metal organic framework-deriving core/shell ZnCo2O4/ZnO nanoarray for better water oxidation. (20th September 2019) - Xiong, Ting; Tan, Ziyu; Mi, Yan; Huang, Qin; Tan, Yan; Yin, Xianhong; Hu, Feilong
Abstract: The high cost and elemental scarcity of precious metals has triggered a search for non-noble-metal catalysts for the oxygen evolution reaction (OER) process. Herein, with the assistance of metal organic frameworks (MOFs), a core/shell ZnCo2 O4 /ZnO nanoarray with an amorphous carbon protecting layer, grown on carbon fiber, was in situ topologically generated. The resulting catalyst shows much enhanced OER performance under alkaline condition, requiring as low as 279 mV of overpotential to reach 10 mA cm −2 current density. Our work may open up a new way for exploiting MOF-derived non-noble-metal electrocatalysts for various electrochemical applications.